Waste to energy in Indonesia: opportunities and challenges - Ni Putu Wulan Romianingsih (Institute for Advanced Science, Social, and Sustainable Future, 2023)
Municipal solid waste management ideally targets reducing the volume of waste stockpiled while recovering as many resources as possible because waste is one of the renewable and biomass energy sources that can generate electricity through the conversion process. Utilizing waste-to-energy (WTE) is one of the waste processing methods recommended by the Indonesian government. As a renewable energy, waste has unlimited availability to be an alternative to fossil fuels. This study aims first to describe the legal basis and policy of WTE in Indonesia; second, to analyze the potential of waste as renewable energy in Indonesia; third, to identify the 2030 SDGs that may be achieved following the WTE Plant installation; fourth, to analyze the challenges in developing WTE in Indonesia. This study is a literature review on secondary data obtained from the Google Scholar and Scopus academic databases. Seeing the characteristics of waste in Indonesia, WTE can be done by thermal or biochemical conversion methods. Both of these methods require pre-processing because the quality of Indonesian waste still needs to improve, which is characterized by high water content and needs to be sorted appropriately.